The relevance of the creative process of design in leadership competencies for sustainable city transitions - Paschini, Maria Caterina Paola (My University, 2017)
In order to address the challenge of leadership for sustainable city transitions, the creative process of design used by architects and the methods used by leaders were investigated. This was done in order to determine the extent of common ground and to shed light on whether the architectural creative process and the associated skills, competencies and attributes can inform the process of leadership. These processes were investigated within the framework of the four stages of the creative process - preparation, incubation, illumination and verification stages - backcasting and phenomenology, which also constituted a theoretical basis of the study. To address the primary data requirements of the study, semi-structured interviews with an architect, a business and a sustainability leader were conducted. Secondary data were collected from writings and interviews of architects and biographies of leaders, together with other published material pertaining to leadership in the sustainable city arena. Data were then analysed based on critical attributes related to the creativity process in relation to leadership. The key findings are that architects follow a specific design methodology, there is no explicit reference to the creative process in their explanations of their design process and their creative process correlates with the creative process as determined in psychology and neuroscience and as experienced phenomenologically. There are similarities in the manner in which architects and leaders envision new solutions, even though their methodologies are not the same. The study concludes that architects and leaders experience the process of creating and pursuing their visions similarly but they manifest differently across the two domains. The findings and conclusions suggest that the well-developed methods used by architects could have relevance in the practice of leadership towards sustainable cities. These methods could be adapted towards developing leadership competencies in transioning cities to the sustainable city of the future. Key words: architects’ design process, creative process stages, leadership, sustainable city transitions, backcasting, phenomenology
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Architecture (Sustainable and Energy Efficient Cities)
Keywords: Sustainable design; Leadership